LINGUISTIC ASPECTS OF UNDERSTATEMENT IN MODERN ENGLISH - V. G. Ivanova (Vestnik MGIMO-Universiteta)
The article focuses on the concept of Understatement as a lingua-cultural category and analyses the main linguistic means of realization of this phenomenon. Besides, some stylistic and pragmalinguistic aspects of Understatement are analyzed from the perspective of a distancing strategy. The researcher is primarily interested in Understatement as a lingua-cultural category relying on historically stipulated cultural traditions of Anglo-Saxon society which gave rise to the forming of the British national character, and which reflect age, gender and social differences of the English. The author does not use the Russian variants of the translation of Understatement in the article, as they do not fully convey all the aspects of denotative and connotative meaning of this concept. Further on it is emphasized that the structure of Understatement is complex, diverse and can be expressed by a variety of lexical as well as grammatical means, among which double negation, modal verbs, the adverbs of degree and particles can often be encountered which are in most cases dependent on the context. From the pragmatic angle Understatement can be used to conceal embarrassment, anxiety or offence. Moreover, Understatement is used while singling out the positive aspects of the communicative situation. The understatement of the positive characteristics of the speaker is reflected in the so called «effect of modesty », which finally boils down to such a strategy as «fishing for compliments», that is an intentional understatement of one’s positive qualities in order to «fish for compliments». Understatement used to and continues to play a special role in the English speech behavior. Its aim is to minimize the impact of the negative factors on the message addressee, to lower the categoricity of the utterance and to take the interlocutor’s interests into account.